EFEKTIFITAS PENGGUNAAN MEDIA Puzzle RUMAH ANGKA UNTUK PEMAHAMAN ANGKA 1 SAMPAI 10 PADA ANAK TUNAGRAHITA RINGAN KELAS II/C DI SLB AMAL BHAKTI Kec. 2X11 ENAM LINGKUNG - Afwan, Zulmiyetri, Yarmis Hasan (Universitas Negeri Padang, 2013)
This research was bacground by the problem that the researcher found at SLB Amal Bhakti, a child mental retaldation mild class II at SLB that have problem in diagnose number from. This research was usool single subjet research, wirh A-B-A design, and technique of data analysis wasused visual graphics analysis, the result gf this research shown that puzzle home numbers media efective toword numbers comprehensior from number one unni ten for the chilld mental retardation mild in mathematic learning class II SLB Amal Bhakti. Observation did in 3 sechon, they were the first, baseline sechon, before given intervensi (A1) that did as many as five times observation, persentase ability to diagnose number from at this condition reside at 0%, second, satirvensi sechon (B) by using puzzle home numbers media, observation did as many as 12 times, persentase ability to diagnose number from at this condition reside at 10%, 30%, 35%, 25%, 25%, 40%, 50%, 65%, 70%, 90% and 90%. Third, at baseline section (A2) did as many as 4 timer observation, and the researcher get the ability of the child in diagnose number from at high persentase reside at 55%, 80%, until 90%, based on the result of this research con tondude that puzzle home number efecctive to improve number comprehensior from number one until ten at child mental retaldation mild in SLB Amal Bhakti Kec. 2x11 enam lingkung. And singgerted from the teacher at the fuhave to use puzzle home number media in number from comprehension at child mental retaldation mild.